CHRONIC GINGIVOSTOMATITIS AND OTITIS EXTERNAL IN A DOMESTIC CAT - Pratanto, Aditya; Widyastuti, Sri Kayati; Erawan, I Gusti Made Krisna (Buletin Veteriner Udayana; Vol. 15 No. 4 August 2023DO - 10.24843/bulvet.2023.v15.i04.p14, 2023)
Feline chronic gingivostomatitis (FCGS) is a chronic inflammation of the mouth that often affects cats. The immune system is thought to be involved in its pathogenesis. The purpose of writing a case report is to provide information on the incidence of FCGS and otitis externa in domestic cats and as a material for consideration in taking action to treat these diseases. The case animal was brought to the Estimo petshop & clinic with a complaint that the cat did not want to eat and drink. According to previous cat owners, it seemed difficult to chew their food, resulting in decreased appetite and drinking, and excessive salivation. This has been going on for a month. The owner also saw the cat often scratching the ear. On clinical examination, the skin turgor is slow, the mandibular lymph nodes are slightly swollen. The buccal mucosa looks red and swollen. Cats also experience hypersalivation and halitosis. On clinical examination, the ear was found to be black, smelly, and wet. Routine haematological examination results showed leukocytosis with neutrophilia. On examination of the ear swab found mites Otodectes cynotis. The therapy given was Ringer's Lactate fluid therapy intravenously, anti-inflammatory dexamethasone at a dose of 0.2 mg/kg BW once a day subcutaneously, a long-acting antibiotic amoxicillin at a dose of 15 mg/kg BW intramuscularly, immunomodulator Viusid©pet with a dose of 1mL/5kg body weight twice a day orally. The therapy given for otitis externa is in the form of topical therapy, namely ear drops containing Pyrethrins as the main ingredient, given three drops twice a day in the left and right ears. Three days after therapy the cat showed an improvement in body condition. Treatment with the given therapy gives good results, signs of gingivostomatitis and otitis externa are no longer observed and cat owners are advised to always pay attention to the cleanliness of the cat's oral cavity by scaling and providing dry food to reduce tartar buildup on the teeth.